SEARCH FOR MARKERS OF CHANGES OF THE SYNTHETIC ACTIVITY OF THYROCYTE UNDER THE INFLUENCE OF IODINE RECEPTION IN IODINE DEFICIENCY CONDITIONS - Ryabukha, O.I. (World of Medicine and Biology, 2018)
An indispensable condition for the activity of a cell is the variety of its states, each of which has its own characteristic – markers, which, according to the degree of completeness of the transformation of one state into another, are divided into markers of primary changes, markers of the majority of changes and markers of final changes. The presented work is devoted to the establishment of those ultrastructural constituents of follicular thyrocyte elements, which when exposed to its synthetic activity by iodine of organic and inorganic chemical nature acquire the signs of markers of the prevailing majority of changes. Qualitative information on the number and condition of thyrocyte organelles associated with the synthesis of thyroid hormones was obtained by viewing the electron diffraction patterns of the thyroid glands of white male rats. After its transformation into quantitative indicators and the subsequent correlation analysis, the revealed correlation connections between organelles were visualized by the construction of correlation portraits, which were analyzed from the positions of cytophysiology. It was established that the synthetic activity of follicular thyrocytes adequately reflects the degree of electron density of their cytoplasm. The most pronounced changes in the state of the cytoplasm are traced after the onset of changes in the number of free ribosomes; the established changes precede the changes in the number of ribosomes bound. This gives grounds to consider the degree of cytoplasm electron density of follicular thyrocytes as a marker of the prevailing majority of changes in their synthetic activity.
Keywords: mathematical technologies in medicine; thyroid gland; thyrocyte; сytophysiology; markers of state changes